The Influence of Instructor Quality and Service Quality on Training Participant Satisfaction Through Brand Image at LPK Axelbit Surabaya - Darmawan*, Herry; Fathorrahman, Fathorrahman; Pradiani, Theresia (Riwayat: Educational Journal of History and Humanities, 2023)
For institutions that provide training services to participants, trainee satisfaction is a very important factor because if participants have attended the training and completed the class level and participants feel satisfied, then they will come back for further classes and can even help recommend services to their friends. This study also takes a brand image as an interference variable because the brand image is an aspect that determines the selection of a training institution and is felt to have an impact on the satisfaction of trainees. This study aims to determine the effect between instructor quality and service quality on trainee satisfaction through brand image interference variables. This type of research uses a quantitative approach and the analysis method used is the path analysis method. The subjects in this study were selected using purposive sampling with categories were participants who had attended training at LPK AXELBIT Surabaya more than twice over the past two years and were taken as many as 100 respondents by the theory of Copper Emery. The results of this study show that 1) there is a significant positive relationship between brand image and trainee satisfaction, 2) there is a positive and significant relationship between instructor quality and brand image, 3) there is a significant positive relationship between service quality and brand image, 4) there is a significant positive relationship between instructor quality and trainee satisfaction, 5) no significant influence was found between variable instructor quality Brand image interference on trainee satisfaction, 6) no significant effect was found between service quality on trainee satisfaction, 7) there was a significant positive influence between service quality on trainee satisfaction through brand image interference variables